Forced Migration and Humanitarian Action: Operational Challenges and Solutions for Supporting People on the Move (Routledge Humanitarian Studies, 2025)
Forced population movements are a defining feature of almost any humanitarian crisis, shaping the design, targeting, and delivery of emergency responses. This book investigates how the evolving situation of different forced migrants is accounted for and addressed in humanitarian action in order to improve their access to support and assistance. Bringing together case studies from Africa, Asia, Europe, and the Pacific, this book focuses on a diversity of operational modalities and types of assistance provided by both traditional and non-traditional humanitarian actors to address the specific needs of displaced children, women, people with disabilities and older people, as well as trafficked migrant workers. This book adopts a broad perspective on humanitarian action, acknowledging how its boundaries are challenged and expanded in forced migration contexts. Its operational and theoretical insights will be useful for a range of readers, from humanitarian and migration researchers and students to practitioners and policymakers.